Methyl α-glycoside of N-thioacetyl-d-neuraminic acid: a potential inhibitor of influenza A virus a 1H NMR study - Machytka, Daisy; Kharitonenkov, Igor; Isecke, Rainer; Hetterich, Peter; Brossmer, Reinhard; Klein, Roger A; Klenk, Hans-Dieter; Egge, Heinz (FEBS letters, 1993)
The binding of influenza A virus hemagglutinin to its cell surface receptor, α-linked 5-N-acetylneuraminic acid (sialic acid), was studied in solution. The effect of structural modifications introduced into the N-acetyl group of the sialic acid on the binding was monitored by determining the dissociation constants by proton nuclear magnetic resonance (1H NMR) spectroscopy. Methyl α-glycoside of N-thioacetylneuraminic acid showed high, whereas the corresponding N-methylcarbamoylneuraminic acid exhibited relatively low binding affinity towards the hemagglutinin.
Elektronische Reproduktion der Druck-Ausgabe 7. Dezember 2001
Gesehen am 24.06.2024